PEMBENTUKAN PORTOFOLIO OPTIMAL PADA SAHAM LQ-45 PERIODE TAHUN 2015 DENGAN MENGGUNAKAN SINGLE-INDEX MODEL - Yuliaty, Erma; Astawinetu, Erwin Dyah; Hadijono, Sri (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2019)
Investors basically pay more attention to risks than returns (profit rates). For this purpose, investors form a portfolio. A trusted portfolio can reduce risk and increase return. In forming a portfolio to reduce risk, it is expected to diversify. Due to rational investors, investors try to get an optimal portfolio, namely a portfolio that will produce the most minimal risk. Whereas in investing in the capital market, investors will be faced with many shares. The LQ-45 index is an index containing 45 stocks with high liquidity and large capitalization. In connection with this matter, in this study a research is conducted on the formation of an optimal portfolio using LQ45 shares and using the Single-Index Model approach. The results of this study indicate that out of 40 LQ-45 stocks that successfully entered as the research object, 10 stock candidates have the potential to form an optimal portfolio. However, after being tested against Zi, only one stock was chosen to form the optimal portfolio, namely AKRA shares. Thus AKRA's hundred percent share becomes the optimal portfolio that generates returns of 0.2531% with a risk of 0.51%. Keywords: LQ-45 Index, Single-Index Model, optimal portfoli